2019
DOI: 10.18805/ijare.a-5202
|View full text |Cite
|
Sign up to set email alerts
|

Effect on physico-chemical and microbial properties of kitchen waste compost (KWC) – using potential fungal inoculant

Abstract: Present study deals with the enrichment of kitchen waste compost (KWC) with Trichoderma harzianum and to analyze its effect on physico-chemical and microbial parameters with respect to different days. The result found that there were minor increments in vital nutrient which required for plant nutrition and healthy development. Statistically, it had also proven that after inoculation or enrichment of KWC, around 14th day it gave better results and could be utilized in organic farming to secure better yield and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Important factors in the process of composting are, particle size of the substrate, moisture content, temperature, pH, C:N ratio, nutrient content and toxic substances. Many studies have reported on the process of composting and quality of compost formed from different types of organic wastes (Goyal et al 2005;Caceres et al 2006;Huang et al 2017;Chaudhary and Mishra, 2019;Jain et al 2019). The present review was undertaken to evaluate the total time taken by different types of organic wastes to convert into compost and the changes in temperature, pH and C:N ratio during the process of composting.…”
mentioning
confidence: 99%
“…Important factors in the process of composting are, particle size of the substrate, moisture content, temperature, pH, C:N ratio, nutrient content and toxic substances. Many studies have reported on the process of composting and quality of compost formed from different types of organic wastes (Goyal et al 2005;Caceres et al 2006;Huang et al 2017;Chaudhary and Mishra, 2019;Jain et al 2019). The present review was undertaken to evaluate the total time taken by different types of organic wastes to convert into compost and the changes in temperature, pH and C:N ratio during the process of composting.…”
mentioning
confidence: 99%